Cultural Identity and Self-Esteem of Indonesian Diaspora Children in Australia - Fitriani, Dyas Noviarale; All Habsy, Bakhrudin (Jurnal Abdimas, 2025)
Global mobility and family migration have placed diaspora children in complex developmental contexts, particularly in relation to cultural identity formation and self-esteem. Living at the intersection of cultures requires diaspora children and adolescents to negotiate personal, ethnic, and national identities simultaneously, which may influence their psychological well-being. This study aims to explore the subjective experiences of diaspora children in constructing cultural identity and its relationship with self-esteem. The study employed an interpretative phenomenological qualitative approach using semi-structured interviews with three diaspora children aged 12–15 years living in Australia from multicultural family backgrounds. Data were analyzed using thematic analysis. The findings indicate that the lived experiences of diaspora children are dynamic and shaped by length of residence in the host country, age, and family background. Participants with early and prolonged cross-cultural exposure tended to demonstrate more stable cultural identity integration, whereas those in the early phase of migration experienced greater identity confusion and fluctuating self-esteem. Integrated cultural identity was associated with more positive self-esteem, which functioned as a psychological resource in socio-cultural adaptation. Furthermore, family support and school environments played a crucial role in fostering identity integration and a sense of belonging. Participants’ narratives also highlighted the need for safe reflective spaces, underscoring the relevance of multicultural counseling in supporting the psychosocial development of diaspora children. This study contributes to the literature by deepening the understanding of the relationship between cultural identity and self-esteem among diaspora children and emphasizes the importance of culturally sensitive counseling approaches in multicultural contexts.